2015
DOI: 10.1007/s12011-015-0485-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imbalance in Trace Element on Thyroid Gland from Moroccan Children

Abstract: The major environmental factor that determines goiter prevalence is iodine status. However, other trace elements like selenium and zinc can influence the thyroid function. Hair samples (n = 68) were collected from goitrous and non-goitrous children aged 8-12 years living in the area of Al Haouz Marrakech-(Morocco). Trace element concentrations (Cr, Fe, Mg, Zn, Se, I) in hair were measured using flame atomic absorption spectroscopy, graphite furnace atomic absorption spectroscopy, and inductively coupled plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In Europe, Wimmer et al [5] reported slightly higher (but not significant) serum selenium levels in normal people than in patients with autoimmune thyroiditis in Lower Austria. A negative correlation between the thyroid volume and Se and I content of hair of goitrous children in Morocco was observed by El-Fadeli et al [6]. …”
Section: Introductionmentioning
confidence: 88%
“…In Europe, Wimmer et al [5] reported slightly higher (but not significant) serum selenium levels in normal people than in patients with autoimmune thyroiditis in Lower Austria. A negative correlation between the thyroid volume and Se and I content of hair of goitrous children in Morocco was observed by El-Fadeli et al [6]. …”
Section: Introductionmentioning
confidence: 88%
“…These enzymes are abundantly present in the TG and help thyroid hormone functioning. A children's study in Morocco found that the average concentration of Se in children with goiter was low and an increase in thyroid volume was associated with Se deficiency (El‐Fadeli et al, 2016 ). Low Se was also linked to the risk of goiter and multiple nodules in European women (Schomburg, 2012 ).…”
Section: Factors That Affect Thyroid Functionmentioning
confidence: 99%
“…Neurocognitive and motor impairments observed in konzo, a motor neuron disease associated with cassava cyanogenic exposure in nutritionally challenged African children, may possibly be driven by the combined effects of cyanide toxicity and selenium deficiency (Bumoko et al, 2015). Selenium and a number of other trace elements may also influence goiter development and general thyroid metabolism (Kishosha et al, 2011;Maouche et al, 2015;El-Fadeli et al, 2016;Gashu et al, 2016). Liver function may be compromised in nickel-plating workers (El-Shafei, 2011).…”
Section: Health Outcomesmentioning
confidence: 99%